Makna Tarian Tradisional Tobunan Katook di Desa Lumbi-Lumbia Kabupaten Banggai Kepulauan - Hanama, Aldi Fitrandi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This research was conducted to determine the meaning and form of nonverbal messages of the Tobunan Katook traditional dance in Lumbi-Lumbia Village, Banggai Kepulauan Regency. This research method is descriptive qualitative. Data collection techniques were carried out by means of observation and in-depth interviews. The number of informants in this research was three people. The results of this research show that the Tobunan Katook dance is a dance that tells about the process of making Tobunan Katook or round pots made of clay. The meaning of kinesics in the Tobunan Katook dance is in the form of facial expressions expressed from the dancer's face, eye contact made by the dancer, and then the dancer's body movements. The meaning of the makatimbuk (clay rolling) movement is that to achieve a goal, cooperation is a very important thing to do. The meaning of the mobasua movement (burning tobunan katook) is that in life, whatever we do we must always remember God who created this entire universe. The moddoon movement (traveling far away or migrating) means that as members of the Sea-Sea tribe, even though they are far from their hometown or are migrating, they will not forget the taste of food cooked in the katook tobunan, so they will still remember their hometown.